111k views
0 votes
If s(x) = x - 7 and t(x) = 4x2 – x + 3, which expression is equivalent to
to (t•s )(x)?

User Seb Kade
by
4.3k points

1 Answer

3 votes

Answer:

(t•s )(x) = 4x^3 - 29x^2 + 10x - 21

Explanation:

(t•s )(x) is the product of functions s and t:

(t•s )(x) = ( 4x^2 - x + 3)(x - 7). Applying the Distributive Property of Multiplication, we get:

(t•s )(x) = 4x^3 - 28x^2 - x^2 + 7x + 3x - 21

which needs to be simplified by combining like terms:

(t•s )(x) = 4x^3 - 29x^2 + 10x - 21

User MDiesel
by
4.8k points